Feasibility Profile of Endometrial Nodule Resection in the Uterosacral and Rectovaginal Ligament - Wirawan, Florencia; Marwali, Luky S (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To know the feasibility of uterosacral and rectovaginal nodule resection in endometriosis patients who underwent laparoscopy surgery in Fatmawati Hospital. Methods: Observational study was done by involving trained and experienced laparoscopist who performed deep infiltrating endometriosis (DIE) nodule resection laparoscopy on uterosacral and rectovaginal ligament. We observed on 35 patients which were histologically proven of DIE. We recorded the total procedure time, surgical complications occurred intra-operative, postoperative, and length-of-stay. The data were described descriptively. Results: Mean (SD) of total laparoscopic procedure time including nodule resection was 200 (SD 52) minutes. There were two procedures (5.7%) with intra-operative complications, one (2.9%) with bowel injury which was converted to laparotomy, and the other one (29%) with intra-operative bleeding so that the operator cancelled nodules resection. Mean (SD) on length of stay after the procedures was 2.5 (2.1) days. On follow up observation, there was not any postoperative complication. Conclusion: Laparoscopic uterosacral and rectovaginal nodules resection in endometriosis patient is feasible to be done by trained and experienced laparoscopic surgeon. [Indones J Obstet Gynecol 2017; 5-1: 42-45] Keywords: endometriosis, laparoscopy, nodule resection